Employers' perspectives on skills falling short, HEIs' education system, and graduates' attributes - Saleh, Hasan; Abdul Wahab, Nurul Asmida (2024)
The objective of this study is to establish the relevance of employability skills that engineers lack, the educational system of higher education institutions, and the key characteristics of graduates from the perspective of Malaysian employers. There is an absence of information on the particular abilities needed by engineers in the workplace, the calibre of the nation’s educational system, and the characteristics of graduates that make them employable. This study used a quantitative technique, with 140 questionnaires delivered to top managers at the organizational level at a Penang, Malaysia-based firm. The survey data was extracted using the Statistical Package for Social Sciences (SPSS) software version 29. Findings indicated employers agreed that engineers must be able to use and keep up with emerging technologies in engineering practice. The results suggest that Higher Education Institutions (HEIs) should update, improve, and deliver the skills with latest industry requirements to make fresh graduates more work-ready. Findings also revealed the important graduates’ attributes to the industry are the ability to balance knowledge, skills, personality, and attitudes. It is suggested that this data analysis would be an important reference for engineers HEIs, and graduates to prepare themselves and take shared responsibility, especially in this challenging economic situation.